Cone-Beam Computed Tomography Assessment of Morphologic and Anatomic Changes of the Nasopalatine Canal: Cross-Sectional Study - Tercanlı, Hümeyra; Taş, Ayşe; Coşan Ata, Gamze (Journal of Dentistry Indonesia, 2023)
Objective: To reveal the morphological and anatomical structure of the nasopalatine canal (NPC) and analyze its measurements via cone-beam computed tomography (CBCT). Methods: A total of 246 CBCT images were included in the study.) NPC diameter, length, angle, distance from the IF to buccal bone (M1), distance from the NF to buccal bone (M2), and the distance from the middle of the NPC to buccal bone (M3) were measured. Statistical significance was assumed at p < 0.05. Results: There was a significant difference between gender and NPC length, M1 and M3 (p = 0.008, p = 0.019 and p < 0.001, respectively), and between the presence of teeth in the anterior maxilla and M1 (p < 0.001). There was a significant difference between the shape of NPC in the coronal plane and NPC angle (p = 0.012) and between the shape of NPC in the sagittal plane and NF diameter, IF diameter, M1 and the M3 (p < 0.001, p = 0.006, p = 0.031 and p < 0.001, respectively). Conclusion: NPC variations, gender, and the presence of teeth in the anterior maxilla could affect NPC measurements. Physicians planning surgery in the anterior maxilla should pay attention to this situation.